2014
DOI: 10.1016/j.dnarep.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DNA ligase III in mitochondria protects cells against oxidative stress and improves mitochondrial DNA base excision repair

Abstract: Base excision repair (BER) is the most prominent DNA repair pathway in human mitochondria. BER also results in a temporary generation of AP-sites, single-strand breaks and nucleotide gaps. Thus, incomplete BER can result in the generation of DNA repair intermediates that can disrupt mitochondrial DNA replication and transcription and generate mutations. We carried out BER analysis in highly purified mitochondrial extracts from human cell lines U2OS and HeLa, and mouse brain using a circular DNA substrate conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 68 publications
(73 reference statements)
0
36
0
Order By: Relevance
“…Reduced levels and activity of LIGIII have been detected in major human neurodegenerative diseases including ataxia telangiectasia (in ATM patient cells and ATM-KO mice) (Sharma et al 2014) and Alzheimer’s disease (Canugovi et al 2013, 2014). LIGIII activity has been reported to be the rate-limiting step of BER in mitochondria (Akbari et al 2014). Thus, regulation of this step should be the best target for stimulation of mitochondrial BER.…”
Section: Bermentioning
confidence: 99%
“…Reduced levels and activity of LIGIII have been detected in major human neurodegenerative diseases including ataxia telangiectasia (in ATM patient cells and ATM-KO mice) (Sharma et al 2014) and Alzheimer’s disease (Canugovi et al 2013, 2014). LIGIII activity has been reported to be the rate-limiting step of BER in mitochondria (Akbari et al 2014). Thus, regulation of this step should be the best target for stimulation of mitochondrial BER.…”
Section: Bermentioning
confidence: 99%
“…ATM deficiency downregulates Lig III and lowers BER capacity in the mitochondria [78]. Lig III is the only DNA ligase in mitochondria and is the rate-limiting enzyme in mtBER[79]. These observations suggest a mitochondrial defect in A-T cells and additional studies of mitochondrial function in A-T is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is only a limited difference in the amount of repair product (upper band), suggesting the rate-limiting step is not nucleotide incorporation. Previous research has reported that ligation activity is rate limiting in BER using this assay (33). The comparable ligation activity can be seen as indirect evidence that the samples have equal input protein concentration.…”
Section: Resultsmentioning
confidence: 71%